Ageing after the Loss of Partner: Exploring the Lives of Widowed Older Adults in Kerala - Laxmi Putran; AK Mohan; Anoop C Choolayil (Social Work and Society)
The loss of a life partner often exerts psychological distress on older adults, which often compounds with other factors, adversely affecting their lives. Living arrangements and social connections can impact the ageing experience of older adults after the loss of a spouse. This descriptive cross-sectional study was conducted among 200 randomly selected older adults from the Kasaragod district of Kerala, India, who had lost their spouses to understand the sense of community and psychosocial profile of the respondents. Data was collected using a questionnaire comprising questions on demographic details and standardised scales for measuring the sense of community, life satisfaction, loneliness and depression. The findings showed that the sense of community had a significant positive correlation with life satisfaction (r = 0.531) and significant negative correlations with loneliness (r = -0.304) and depression (r = -0.603). Loneliness and depression had a significant positive correlation (r=0.447) with each other. Satisfaction with life had significant negative correlations with loneliness (r = -0.529) and depression (r = -0.689). Also, there were significant differences in the psychosocial profile of the respondents based on gender. Female respondents had significantly higher loneliness and depression and significantly lower life satisfaction and sense of community than their male counterparts. The findings suggest that widowed older adults experience significant psychosocial distress, and this distress is disproportionately affecting women. Hence, gender-informed interventions that target improving the social connectedness of older adults can contribute to better mental health outcomes.